Developing a framework for youth empowerment to prevent smoking behavior in a rural setting: study protocol for a participatory action research. Issue 1 (23rd November 2020) - Trisnowati, Heni; Ismail, Djauhar; Padmawati, Retna Siwi; Utarini, Adi
Abstract : Purpose: There is limited research examining community-based youth empowerment that addresses smoking prevention in the rural Indonesian context. This paper describes participatory action research (PAR) applied to develop a framework for empowering youth aged 17–25 years toward smoking prevention. This research conducted in the Indonesian rural community setting was divided into four stages: diagnosing, planning action, taking action and evaluating action. Design/methodology/approach: PAR was chosen as the approach to developing a framework for youth empowerment in smoking prevention programs. In this study, the PAR cycle started with a prestep stage through interviews with village heads, community leaders, youth organization organizers, observations of target resources and observations of participation in youth activities as well as forming teamwork with target participants. The diagnosis stage consists of three activities, that is, focus group discussions with youth groups of male and female, youth assessment of empowerment domains through the Participatory Rural Appraisal (PRA) with the Empowerment Assessment Rating Scale (EARS) and measuring individual and group involvement levels related to the smoking behavior prevention program by questionnaire. The EARS assessment results were presented in the action planning stage, followed by a discussion on youth empowerment plans and strategies. In the action stage, activities and programs are planned according to the planning discussion, that is: training in healthy life skills (outbound and training) and initiating youth health programs without smoking called "Remaja Berdaya Sehat Tanpa Rokok" (Empowered Youth Healthy Without Smoking) or the JayaStar Program. After these community participation activities, the evaluating action stage will assess the empowerment domain in the youth groups, conduct focus group discussions with parents, evaluate the impact of empowerment on individual and group changes with a questionnaire and facilitate self-reflection by the youth community called Madiska. Findings: This protocol describes a doctoral research project on developing a youth empowerment framework in smoking prevention programs through PAR. The intended study will provide valuable information on the planning, implementation and evaluation of youth empowerment in the prevention of smoking behavior. Originality/value: This research project is expected to contribute to the literature relating to PAR for rural settings and the use of empowerment strategies to prevent youth smoking behavior. The results can be replicated in the same settings, but the process of empowerment must still be adapted to the characteristics and local wisdom of the community.